2020
DOI: 10.1002/jsfa.10295
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ovalbumin‐derived peptides as multi‐target inhibitors of AChE, BChE, and BACE1

Abstract: BACKGROUND Alzheimer's disease (AD) is a kind of progressive neurodegenerative disease that affects the elderly. There is no ideal treatment for AD. Thus, the purpose of this study is to identify anti‐AD peptides from ovalbumin. RESULTS The potential tripeptides IEK, LYR, and CIK were selected for molecular docking. The ‘‐CDOCKER_Energy’ values of the best docking positions of the tripeptide IEK, LYR, and CIK interacting with acetylcholinesterase (AChE) were 93.8119, 86.9556 and 73.6370 kcal mol−1, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In molecular docking, the higher the ‘-C DOCKER interaction energy’ value, the more favorable the binding ( Yu et al, 2020 , Yu et al, 2020 ). Table 3 shows the binding energies obtained from the molecular docking of peptides with SARS-CoV-2 M pro .…”
Section: Resultsmentioning
confidence: 99%
“…In molecular docking, the higher the ‘-C DOCKER interaction energy’ value, the more favorable the binding ( Yu et al, 2020 , Yu et al, 2020 ). Table 3 shows the binding energies obtained from the molecular docking of peptides with SARS-CoV-2 M pro .…”
Section: Resultsmentioning
confidence: 99%
“…Pepsin (EC 3.4.23.1), Trypsin (EC 3.4.21.4), and Chymotrypsin (EC 3.4.21.1) are three typical enzymes in the gastrointestinal tract, which were chosen for proteolysis in the present study ( Yu, Dong, et al, 2020 ). The amino acid sequence of tuna skeletal myosin heavy chain (Accession of NCBI: BAA12730.1) was chosen from the National Center for Biotechnology Information (NCBI) database (https://www.ncbi.nlm.nih.gov/).…”
Section: Methodsmentioning
confidence: 99%
“…( Nongonierma, Mooney, Shields, & Fitzgerald, 2013 ). Many studies have confirmed the reliability of in silico screening methods, which can be regarded as valid alternatives to classic methods ( Fu et al, 2016 , Yu et al, 2020 , Yu et al, 2020 , Zhao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 98%
“…The cholinergic hypothesis considers that the level of acetylcholine in the brain of AD patients is fairly low. This can happen because of the degradation produced by two cholinesterases: the first one is the true cholinesterase, AChE, and the other one is a pseudocholinesterase, BChE [ 98 ]. The AChE inhibitors are currently the most prescribed drug class for the treatment of AD [ 99 , 100 ].…”
Section: The Antioxidant Properties Of Egg-derived Peptidesmentioning
confidence: 99%
“…The AChE inhibitors are currently the most prescribed drug class for the treatment of AD [ 99 , 100 ]. In addition to the cholinergic hypothesis, Yu et al considered the Abeta hypothesis (already described in paragraph 2), and they evaluated some ovalbumin-derived peptides inhibiting activity for BACE1 [ 98 , 101 ].…”
Section: The Antioxidant Properties Of Egg-derived Peptidesmentioning
confidence: 99%